1958
DOI: 10.1038/1811054a0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Speed of Rotation of the Earth since June 1955

Abstract: The Editors do not hold themselves responsible jO'I' opinions expressed by their cO'l'Tespondents. No notice is taken of anonymous communications. Variation in theSpeed of Rotation of the Earth since June 1955 TIME and frequency comparisons have. been ma.de since June 1955 between the National Physical Laboratory, Teddington, and the U.S. Naval Observatory, Washington, with the ultimate purpose of establishing the value of the transition frequency of cresiuro, {4,0) ~ {3,0), in terms of the second of Epheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1960
1960
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Even though TAI was set to be identical with UT on 0 January 1958, TAI steadily diverged ahead of UT. The very team that so precisely calibrated the SI second to the lunar ET second reported that the UT second was larger than the lunar ET second by using the same calibration data from 1955 through 1958 [30,31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though TAI was set to be identical with UT on 0 January 1958, TAI steadily diverged ahead of UT. The very team that so precisely calibrated the SI second to the lunar ET second reported that the UT second was larger than the lunar ET second by using the same calibration data from 1955 through 1958 [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…The very team that precisely calibrated the lunar ET second for the SI (or atomic) second later reported from the same data of lunar observations, cesium frequencies and UT observations that the UT second was longer than the lunar ET second [30,31]. The calibration for the cesium clock to the ILE started January 1955 and lasted 3 ¼ years.…”
Section: Brief History Of Universal and Ephemeris Timescalesmentioning
confidence: 89%
See 1 more Smart Citation
“…Atomic and molecular standards of frequency are being used to control standard frequency transmission and to study changes in the speed of rotation of the Earth. The cesium standard built by L. Essen and J. V. L. Parry at the National Physical Laboratory, Teddington, in 1955 has an apparent stability of 1 part in io 10 [1]. A cesium standard, called the Atomichron, is being built commercially in the United States.…”
Section: Heure Clock a N D Atomic Standardsmentioning
confidence: 99%
“…Naval Observatory, Washington. The results were published in two papers [1,2]. The frequency obtained is 9 192 631 770 cycles per second.…”
Section: Zi Ka Weimentioning
confidence: 99%